A nickel-mediated oxidative α-C(sp3)–H functionalization of amides with allylic alcohols terminated by radical 1, 2-aryl migration. Issue 4 (25th November 2014) - Song, Ren-Jie; Tu, Yong-Qiang; Zhu, Dao-Yong; Zhang, Fu-Min; Wang, Shao-Hua
Abstract : A Ni-mediated oxidative C(sp 3 )–H functionalization of N, N -substituted amides with α, α-diaryl allylic alcohols through a radical 1, 2-aryl migration process has been developed. This process features a broad substrate scope and excellent functional group tolerance. Abstract : A Ni-mediated oxidative C(sp 3 )–H functionalization of N, N -substituted amides with α, α-diaryl allylic alcohols through a radical 1, 2-aryl migration process has been developed. This process features a broad substrate scope and excellent functional group tolerance. Notably, γ-amino ketones containing an all-carbon quaternary center were synthesized under these conditions in moderate to good yields.